2021
DOI: 10.1002/anie.202012877
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Promoted C–N Coupling of Aryl Halides with Nitroarenes

Abstract: A photochemical C-N coupling of aryl halides with nitroarenes is demonstrated for the first time. Catalyzed by a Ni II complex in the absence of any external photosensitizer, readily available nitroarenes undergo coupling with a variety of aryl halides, providing a step-economic extension to the widely used Buchwald-Hartwig C-N coupling reaction. The method tolerates coupling partners with steric-congestion and functional groups sensitive to bases and nucleophiles. Mechanistic studies suggest that the reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 56 publications
(28 reference statements)
1
79
0
Order By: Relevance
“…22,23 This observation was expanded to a synthetic protocol for C-O and C-N cross-couplings using UV-light irradiation. 24,25 More recently, pulse radiolysis together with spectroelectrochemistry indicated that Ni 0 /Ni II comproportonation generates a Ni I bipyridyl species that rapidly undergoes oxidative addition with iodobenzene. 21 Moreover, Nocera and coworkers showed that sub-stoichiometric amounts of zinc can be used instead of a photocatalyst and light for C-N and C-O cross-couplings.…”
Section: Main Introductionmentioning
confidence: 99%
“…22,23 This observation was expanded to a synthetic protocol for C-O and C-N cross-couplings using UV-light irradiation. 24,25 More recently, pulse radiolysis together with spectroelectrochemistry indicated that Ni 0 /Ni II comproportonation generates a Ni I bipyridyl species that rapidly undergoes oxidative addition with iodobenzene. 21 Moreover, Nocera and coworkers showed that sub-stoichiometric amounts of zinc can be used instead of a photocatalyst and light for C-N and C-O cross-couplings.…”
Section: Main Introductionmentioning
confidence: 99%
“…Knochel and co‐workers, [10] Kürti and co‐workers, [11] and Niggemann and co‐workers [12] have demonstrated reductive conversion of nitroarenes with organometallic compounds to N ‐arylamines (Scheme 1A, a). Recently, Xue and co‐workers reported a photochemical C−N coupling of aryl halides with nitroarenes catalyzed by a Ni(II)‐aryl complex in the absence of any external photosensitizer (Scheme 1A, b) [13] . Particularly noteworthy is the groundbreaking research on the reductive arylation of nitroarenes with boronic acids, that is, organophosphorus [14] catalysis reported by Radosevich and co‐workers and molybdenum [15] catalysis reported by Sanz and co‐workers (Scheme 1A, c).…”
Section: Methodsmentioning
confidence: 99%
“…Through DFT calculation, nitrosoarenes were evidenced as the key intermediates in the reaction (Figure 1B) [18,19] . Very recently, Xue and co‐workers disclosed a Ni‐catalyzed and light‐promoted C−N coupling of aryl halides with nitroarenes under 390 nm LEDs at 70 °C (Figure 1C) [20] …”
Section: Introductionmentioning
confidence: 96%